2014
DOI: 10.22323/2.13030305
|View full text |Cite
|
Sign up to set email alerts
|

Public relations as science communication

Abstract: Public communication from research institutions often functions as both science communication and public relations. And while these are distinct functions, public relations efforts often serve as science communication tools. This is because successful science communication and public relations efforts for research institutions both rely on finding shared language and disseminating findings in context. Public communication from research institutes: is it science communication or public relations? Is there a dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…Thus, we agree with Shipman (2014) when he states that a press release can be both a public communication tool of science and an institutional marketing tool, because it gives journalists access to scientific results produced in research institutions, encouraging them to make their coverage based on these data, while these same institutions gain prestige in the media sphere. We conceived the hybrid model of science communication of the Agência Bori in this duplicity.…”
Section: /17supporting
confidence: 61%
“…Thus, we agree with Shipman (2014) when he states that a press release can be both a public communication tool of science and an institutional marketing tool, because it gives journalists access to scientific results produced in research institutions, encouraging them to make their coverage based on these data, while these same institutions gain prestige in the media sphere. We conceived the hybrid model of science communication of the Agência Bori in this duplicity.…”
Section: /17supporting
confidence: 61%
“…With the above caveats in mind, this study has helped advance our understanding of a critical area at the intersection of social media and science public relations. Prior research has identified the key role of public relations practices in facilitating effective science communication (Borchelt & Nielsen, 2014;Shipman, 2014), and the public has increasingly shifted toward online sources such as blogs and social media for news and information (Pew Research Center, 2016;Su, Akin, Brossard, Scheufele, & Xenos, 2015). The ubiquity and interactive characteristics of social media provide unprecedented opportunities for organizations to actively communicate with the public; yet, despite the importance of understanding science public relations practitioners' social media usage patterns (Lee et al, 2017;Lee & VanDyke, 2015), substantial gaps in this line of research remain.…”
Section: Discussionmentioning
confidence: 99%
“…Public relations techniques often serve as science communication tools, insofar as scientific organizations utilize them to achieve strategic goals and facilitate dialogic communication with the public (Shipman, 2014). Operating within the broader paradigm of science communication, science public relations efforts such as news releases and blog posts may help increase public engagement with science, enhance public understanding and awareness of it, and embed it in day-to-day culture (Sanchez-Mora, 2014;Shipman, 2014). Moreover, effective public relations aids science organizations in cultivating and maintaining the trust of their stakeholders (Borchelt & Nielsen, 2014).…”
mentioning
confidence: 99%
“…Atualmente, para que uma instituição seja bem-sucedida tem de ter a devida visibilidade e reconhecimento por parte dos cidadãos. De facto, para atrair os melhores alunos e os melhores cientistas, as grandes instituições têm de ter uma atitude pró-ativa na divulgação e promoção das atividades por si desenvolvidas, quer ao nível do ensino quer da investigação (Shipman, 2014). Por exemplo, é necessário desenvolver estratégias fortes e assertivas de "apresentação" da Escola, promovendo, por exemplo, visitas aos espaços de investigação e criação de conhecimento.…”
Section: Promoção E Divulgaçãounclassified